(untitled) (Fiep Bulletin - online, 2019)
The central idea of this work is to analyze by means of references the importance of Psychomotor Re-education inphysical education classes and your relevance as psychomotor practice. Having as main objective to contribute to the integraldevelopment of students, proposing issues and ideas related to learning and psychomotor re-education in physical educationclasses. Physical education teachers today fall short regarding the teaching of psychomotricity in the early years of earlychildhood education, and in this sense it is necessary the intervention possibilities, or psychomotor rehabilitation to remedy thelearning difficulties through the psychomotor practice, which explores bodily functions. We know that learning and thepsychomotricity is a global process that involves the whole body, because it is through the physical education classes that we willlook at the issues and the cognitive, affective-emotional link and motor in the actions and in the school learning process.